2011
DOI: 10.1080/07370016.2011.614827
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health Disparities Through Patient Education: The Development of Culturally-Tailored Health Education Materials at Puentes de Salud

Abstract: The availability of culturally appropriate written health information is essential for promoting health in diverse populations. Lack of English fluency has been shown to negatively impact health outcomes for Latinos in the United States. The authors conducted a needs assessment at a clinic serving Latino immigrants, focusing on patients' health and previous experiences with written health information. Based on these results and a literature review, we developed 10 Spanish language brochures to better serve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Clinicians often address multiple health behaviors simultaneously and supplement office visits with additional health education through written materials, such as patient information sheets or brochures [1, 2]. Although these sheets are considered standard of care, the content and readability may not necessarily benefit patients with cultural or economic differences or lower literacy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians often address multiple health behaviors simultaneously and supplement office visits with additional health education through written materials, such as patient information sheets or brochures [1, 2]. Although these sheets are considered standard of care, the content and readability may not necessarily benefit patients with cultural or economic differences or lower literacy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Harvey and O’Brien (2011) have suggested that Hispanics desire more options for health education than are currently available to them. This suggestion is consistent with our study’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that many Hispanics prefer to receive health-related information through sources of media, such as the Internet, radio, television, and newspaper/magazines (De Jesus, 2013; Livingston et al, 2008; Pena-Purcell, 2008). Health education designed for Spanish speakers is often delivered using low-cost passive methods, such as videos or written materials, or it is provided in person by a physician, nurse, patient navigator, or other health care worker (Harvey & O’Brien, 2011; Livingston et al, 2008). Videos and written materials typically require few resources to deliver, whereas delivery of health education by a health care worker can be time consuming (Aronson, Plass, & Bania, 2012; Kools, Ruiter, van de Wiel, & Kok, 2007; Livingston et al, 2008; Powell, Edelson, O'Leary, Christianson, & Henrich, 2011).…”
mentioning
confidence: 99%
“…Readability levels are based on the average sentence length and the percentage of multisyllabic words in phrases. We incorporated the use of pictures and culturally relevant graphics into the teaching materials for this low‐literacy Kaqchikel population to facilitate comprehension (Coronado et al., ; Garcia, Chismark, Mosby, & Day, ; Harvey & O'Brien, ; Heinrich, ). A PowerPoint presentation was created for each topic area with a focus on maintaining the reading level at approximately fourth to fifth grade level or lower when possible.…”
Section: Research Questionmentioning
confidence: 99%